PENGARUH PROMOSI (PROMOTION) TERHADAP KEPUTUSAN SISWA MEMILIH SEKOLAH SATUAN PENDIDIKAN MUADALAH (SPM) ULYA BLOKAGUNG BANYUWANGI - Mamlukhah Mamlukhah; Agus Setiawan (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
The purpose of this study was to determine how much influence the promotion carried out by the manager of the Mudalam Education Unit (SPM ULYA) Madrasah Diniyyah Al Amiriyyah Pondok Pesantren Darussalam Blokagung. The research method used in this research is descriptive quantitative. The results of this study are: (1) the results of the questionnaire about promotion with 53 respondents are said to be very good with a perc[1]entage of 88,60% (2) the results of the questionnaire on student decisions of Mudalam Ulya are also very good with a percentage of 88,86%. (3) the effect of promotion on the decision of Mudalam Ulya Darussalam students to choose a school in the Al Amiriyyah Ulya Darussalam Mudalam Education Unit (SPM) for the 2020/2021 academic year is 90,63% with a t-count result of 0.952 then it is between 0.80-1.00 means very strong.